Biodegradation of azo dyes by bacterial or fungal consortium and identification of the biodegradation products - Wafaa M. Abd El-Rahim (Egyptian Journal of Aquatic Research, 2021)
Fifteen azo dyes were subjected to microbial degradation by four fungal strains and their mixtures as well as five bacterial strains and their mixtures. The biodegradation efficiency was determined by LC/MS/MS analysis. The most active bacterial strain was B. subtilis, where it showed the highest biodegradation capacity (71.8% to 100%) of eight azo dyes. Bacterial strain B. brevis came next to it. However, the consortium of the five bacterial strains gave lower degradation percentages. On the other hand, the fungal strains and their consortium were more potent in biodegradation of all tested azo dyes, where ten azo dyes were completely (100%) degraded by the consortium. Two of widely used azo dyes, direct violet and methyl red, were further studied in relation to the intermediate biodegradation products by each of the tested fungi and bacteria as well as the bacterial and fungal consortia using GC/MS/MS. The major biodegradation product of methyl red was 2-amino benzoic acid by all of the tested bacterial strains and A. niger, while the major biodegradation products of direct violet by both bacteria and fungi were ethanol, 2(2-butyxyethoxy), followed by 4- methyl benzoic acid and phenol, 2,4-bis (1,1-dimethyl ethyl). The results of this study suggest the successful use of the four fungal consortium for the biodegradation of the azo dyes. These findings are important to design bioremediation technology for treating the azo dye residues.